Biomimetic and Biohybrid Systems: Third International Conference, Living Machines 2014, Milan, Italy, July 30-August 1, 2014, Proceedings - Duff, Armin; Lepora, Nathan F; Mura, Anna; Prescott, Tony J; Verschure, Paul F. M. J (Lecture Notes in Computer Science, 2014)
This book constitutes the proceedings of the Third International Conference on Biomimetic and Biohybrid Systems, Living Machines 2014, held in Milan, Italy, in July/August 2014. The 31 full papers and 27 extended abstracts included in this volume were carefully reviewed and selected from 62 submissions. The topics covered are brain based systems, active sensing, soft robotics, learning, memory, control architectures, self-regulation, movement and locomotion, sensory systems and perception.